Development of Thermal Energy Harvesting from Air Conditioner for Self-Powered Smart Home Appliances - Moorthy, Thines; Sy Yi, Sim; Zambri, Nor Aira (Progress in Engineering Application and Technology, 2021)
Recycling energy is a viable option for establishing a green environment in today's society. Air conditioner consumes the most energy on a global scale. Air conditioning is commonly used to maintain a comfortable interior temperature. Split unit air conditioning systems are popular in Malaysia for small-area applications. The heat released by the condensing unit, on the other hand, is lost to the environment. In this project, one Peltier device was designed by utilising the thermoelectric generator (TEG) module. The purpose of this project is to develop the Peltier device for thermal harvesting from a condenser unit and converting it into usable electricity. The designed Peltier device was sandwiched between two copper plates. The sandwiched TEG is being placed at two different locations which are at the discharge pipe and at the heat tank. The performance of two different locations is investigated and the best location will be chosen based on the effectiveness and performance of the TEG. In order to validate the proposed design, five Peltier were placed between copper plates in random order to harvest the thermal energy. After 30 minutes of operation, the TEG placed at split unit air conditioner condenser produced a maximum of 3 V. The 3V is then stepped up to 13V which is used to charge the battery. The voltage from the battery is then directed to the socket outlet with the help of an inverter. The use of TEG to gather heat and convert it to power demonstrates that a heat recovery is a viable option. The current generated might be suitable for home appliances usage.